PENGELOLAAN TANAMANTERPADU (PTT) PADI SAWAH DI LOKASI PRIMA TANI - Rusdin Rusdin; Suharno Suahrno (Agro Ekonomi, 2010)
The review paper on application of the Integrated Cropping System (ICS) has been accomplished. The objective of this study was to identify this system relate to the increasing of rice productivity and farmer's income. Indonesian Agency of Agricultural Research and Development (IAARD) has released and developed the integrated cropping system approach which could improve productivity and farmer's wealth. Results on tria plot in Southeast Sulawesi revealed that ICS could increased the productivtty around 48,57 - 80,30 %/ha/growing season otherwise improving income around Rp. 2,40 - 2,47 million/ha/growing season. The simmiler results were showed in some other provinces such as Bante, Maluku, NTB Central Java, and West Java which ICS could increased the productivity around 0,33 - 82,7 % or improving farmer income around Rp. 0,4 - 3,5 millions/ha/growing.